PERBANDINGAN PUISI INDONESIA â€œKARAWANG-BEKASIâ€ KARYA CHAIRIL ANWAR DAN PUISI SPANYOL â€œMI ULTIMO ADIOSâ€ KARYA JOSÃ‰ RIZAL - Monica, Laura; Fitriyani, Dwi; Indriyani, Dewi; Raissa Zahara, Sella (Pascasarjana, Universitas Negeri Gorontalo, 2023)
The aim of this research article is to obtain results of a literary comparison of the poem entitled